2022
DOI: 10.1186/s12957-022-02616-z
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy evaluation of combining gastroscopy, multi-slice spiral CT, Her-2, and tumor markers in gastric cancer staging diagnosis

Abstract: Background To evaluate the diagnostic accuracy of single gastroscopy, multi-slice spiral CT, HER-2 or tumor markers, and their combination in the diagnosis of gastric cancer. Methods A total of 98 patients with gastric cancer were selected as the research subjects. All patients underwent preoperative gastroscopy, MSCT, and the expression levels of HER-2, CEA, CA199, CA724, and CA242 were detected. A control group of 98 normal adults was selected to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…However, the sensitivity and speci city of existing tumor markers are not su ciently effective, and the search for optimal tumor markers for detecting gastric cancer continues. [14] Recent years have seen the emergence of new tumor markers, such as CST4, which have been shown to have high diagnostic value for gastrointestinal cancers [15] . Some studies have found that combining certain tumor markers can enhance the diagnostic value for gastric cancer [16] , such as the combination of gastrin-17 with CEA, CA125, and CA19-9 [17] .…”
Section: Discussionmentioning
confidence: 99%
“…However, the sensitivity and speci city of existing tumor markers are not su ciently effective, and the search for optimal tumor markers for detecting gastric cancer continues. [14] Recent years have seen the emergence of new tumor markers, such as CST4, which have been shown to have high diagnostic value for gastrointestinal cancers [15] . Some studies have found that combining certain tumor markers can enhance the diagnostic value for gastric cancer [16] , such as the combination of gastrin-17 with CEA, CA125, and CA19-9 [17] .…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study reveal that the later the stage, the higher the risk ratio (HR), and the later the stage indicates that the deeper the tumor invasion of the intestinal wall, the greater the chance of vascular and nerve invasion and the increased probability of metastasis in the distant organs of the tumor cells. CEA is a gastrointestinal cancer marker that is involved in disease diagnosis and the evaluation of disease prognosis ( 15 – 17 ). Several previous studies have found CEA positivity to be a poor prognostic factor in the gastrointestinal tract ( 18 ), which is consistent with the results of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that EUS achieves a high overall accuracy in T stage assessment, with a sensitivity of 86% (32). Zhao et al demonstrated that the accuracy of staging using multi-slice spiral CT images and gastroscope can reach 83.67% through statistical analysis (33). Guan et al employed Yolov5-based DetectionNet for staging gastric cancer on arterial phase CT images, achieving an average accuracy of 0.909 (34).…”
Section: Preoperative Diagnosis Of Gc Has Been a Focal Point Of Researchmentioning
confidence: 99%